Associations between benign cutaneous nevi and risk of Type 2 diabetes mellitus in men and women: results from two prospective cohort studies. Issue 7 (29th December 2016) - Dai, H.; Sun, Q.; Zhang, C.; Zhang, X.; Li, W.‐Q.; Manson, J. E.; Hu, F. B.; Song, Y.
Abstract: Aim: To examine the association of cutaneous nevi with Type 2 diabetes risk. Methods: We prospectivly examined the associations between nevus count and risk of Type 2 diabetes among 26 240 men (1988–2010) from the Health Professionals Follow‐up Study and 67 050 women (1986–2010) from the Nurses' Health Study. Information on the numbers of cutaneous nevi on arms at baseline and incident cases of Type 2 diabetes was collected using validated questionnaires. Results: During 1 879 287 person‐years of follow‐up, we documented 9040 incident cases of Type 2 diabetes. After adjustment for age, BMI and other diabetes risk factors, greater number of nevi was associated with higher risk of Type 2 diabetes. Multivariable‐adjusted hazard ratios for <1, 1–5, 6–14 and ≥15 nevi were 1.00 (reference), 1.02 (95% CI 0.93, 1.13), 1.08 (95% CI 0.88, 1.34) and 1.57 (95% CI 1.15, 2.15), respectively, for men ( P for linear trend = 0.01), and 1.00 (reference), 1.07 (95% CI 1.02, 1.13), 0.98 (95% CI 0.87, 1.10), and 1.25 (1.01, 1.54), respectively, for women ( P for linear trend = 0.05). This positive association remained consistent across subgroups stratified by age, BMI, multivitamin use, smoking status, alcohol, physical activity, history of hypercholesterolaemia, family history of diabetes, history of hypertension and menopausal status (in women). Conclusions: Cutaneous nevus count may represent a novel marker for development of Type 2 diabetes, suggesting a possible unique melanocytic nevus‐related mechanism in the pathogenesis of Type 2 diabetes. Further studies are warranted to confirm the findings and to investigate the underlying mechanisms. What's new?: Based on our previous findings on the association between endogenous sex hormone biomarkers and Type 2 diabetes mellitus, we first postulate a hypothesis that melanocytic nevus count may be a phenotypic marker of Type 2 diabetes risk via its link with sex steroid hormones. We prospectively investigated whether and to what extent the number of cutaneous nevi is related to risk of Type 2 diabetes in both men and women, based on two large well‐characterized cohort studies, the Health Professionals Follow‐up Study and the Nurses' Health Study. We found the number of nevi was significantly and positively associated with risk of Type 2 diabetes in both men and women. Our findings suggest that mole count could be a novel predictor for risk of Type 2 diabetes, independently of known diabetes risk factors.